The determination of acceptable Hippopotamus (Hippopotamus, Amphibius, Linn.) densities in the Crocodile River, outside the Kruger National Park - Eksteen, J.J. (My University, 1993)
The aim of the study was to provide a basis for the determination of acceptable hippo densities along the Crocodile River, outside the Kruger National Park. Hippo densities have to be acceptable to land-user~, who suffer hippo damage, and to the conservation authority, responsible for the resources along the river. Hippo nllmbers and distribution in the study area were determined by using a combination of aerial census and ground count. The hippo population number was estimated at 88 animals. Hippo distribution was influenced by flow speed of water. No hippos were observed in river sections with steep gradients, (>6.0 m/km) , while major herds were observed at low gradients «3.5 m/km). A mean density of 0.6 hippo per km was calculated, with a maximum of 2,5 hLppoe Zkm at Kaapmuiden, next to the Kruger National Park. TPA Nature Conservation records on hippo complaints were analyzed, and no relationship between the occurrence of hippo damage and hippo density could be found. There were strong indications that hippo damage are caused by individual problem hippo , The majority of land-users (92 %) supported the conservation of hippos. The size of the area available to hippo was determined for distances of 5 kn. up- and downriver from the major hippo herds. hippo could move away from the river was 336 restriction when compared to the generally assumed hippo grazing range of 3.2 km. Hippo access to grazing was assessed by determining the effective grazing area.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree Master of Science in Quantitative Conservation Biology, 1993
Keywords: Hippopotamus--Limpopo River; Animal populations--Limpopo River; Mammal populations--Limpopo River